Analisis Peran Guru dalam Meningkatkan Motivasi Belajar pada Siswa Sekolah Dasar - Afifah Azahra; Dara Rafina Aisyah; Mutiara Faazal Fitriah; Non Dwishiera Cahya Anasta (Journal on Education, 2025)
Students' learning motivation in elementary schools is still lacking, which can be seen from the phenomenon of students showing passive attitudes during the learning process, such as laziness, lack of enthusiasm, and lack of attention. This research aims to examine the role of teachers in increasing students' learning motivation. Through a Systematic Literature Review (SLR) and bibliometric approach, this research analyzes various studies that have been conducted previously. The study used reference management software, Publish or Perish (PoP) to collect research data. The results showed that motivation is a key factor in student learning success. Motivation is not only related to learning initiative, but also intensity and perseverance in achieving learning goals. Teachers, as learning facilitators, have a central role in generating and maintaining students' learning motivation. This study highlights the importance of creating a conducive, interesting and supportive learning atmosphere for students. Thus, teachers can be effective motivators in encouraging students to achieve their optimal learning potential.